THE EFFECTIVENESS OF COMPLEX APPLYING PREPARATIONS OF DIFFERENT ORIGIN AGAINST FUSARIUM ROOT ROT OF WINTER WHEAT - Gritsyuk, N. V.; Derechа, O. A.; Bakalova, A. V.; Skladanovskа, Ya. M.; Popelyanska, T. V. (Scientific Progress & Innovations, 2019)
The article presents the results of two-year field and laboratory studies as to the effect of pre-sowing complex treatment of winter wheat seeds with bio-fungicide, growth stimulator, chemical preparation on the cultivation of fusarium root rot and yield formation of the crop. Fusarium root rot is a widely spread disease in the wheat field. It is quite harmful in the seedling phase, slowing down their growth and development. Soil and seed infections, as well as temperature, soil moisture, and the physiological state of plants play a signif-icant role in the spread of this disease. The most effective measure of winter wheat crop protection against soil, seed, and aerogenic infection is seed treatment. The correct combination of biological and chemical preparations at pre-sowing treatment of seeds makes it possible not only to reduce the incidence of fusarium root rot and significantly increase the crop yields, but also to reduce pesticide load on plants and soil. Such complex using of preparations will considerably improve the environmental state of agro-landscapes and the environment. It was established at treatment of winter wheat seeds with Emistim C, (10 ml/t) growth stimula-tor, the seedling length increases by 1.7 cm, the germination energy also increases by 3 %, the laboratory germination – by 4 %. According to the results of phyto-examination of the seeds treated with the tank mix-ture of chemical and biological preparations, the seed share affected with the fungi of Alternaria spp. genus was 0–2 %, with the fungi of Fusarium spp. genus – 0–1 %. Technical efficiency of applying the biological preparation, growth stimulator both individually and in combination with the chemical preparation for win-ter wheat seed treatment has been determined. The index of technical efficiency was the highest in the vari-ant where Lamardor 400 FS TN was applied (0.15 l/t) with adding the Phytohelp bio-fungicide, (1.0 l/t) – (89.5 %), whereas the application Phytohelp p, (1.0 l/t) and Emistim C, (10 ml / t) preparations ensured the technical efficiency of 73.0 % and 59.0 %, respectively. It was revealed that the highest yield increase of winter wheat was obtained at the complex application of Lamardor, 400 FS TH, (0.15 l/t) in combination with Phytohelp bio-fungicide, (1.0 l/t) and Emistim C growth stimulator, (10 ml/t) – 0.9 and 0.8 t/ha, respec-tively.